Combination of EDAS Method and Entropy Weighting in the Selection of the Best Customer Service - Setiawansyah Setiawansyah (PT. Tech Cart Press, 2024)
Customer service is an integral part of a business that is responsible for providing service, support, and solutions to customers before, during, and after the purchase process. Selecting the best Customer Service is an important process in supporting a company's success in providing an exceptional customer experience. The main problems in assessing the best customer service are often related to subjectivity and gaps in data collection and analysis. Less clear or unstandardized assessment criteria can lead to bias, especially if the evaluation relies on the opinion of a particular individual without any supporting quantitative data. The purpose of this study is to apply the combination of EDAS method with Entropy Weighting in the selection process of the best customer service to produce an objective, transparent, and efficient scoring system by combining Entropy's ability to automatically determine the weight of criteria based on existing data, and using EDAS to evaluate and rank alternatives based on their distance from the average solution. Based on the ranking results in the best customer service alternative ranking, Andi occupies the first position with the highest score, which is 0.6017. In second place is Rina with a score of 0.5728, followed by Budi in third place with a score of 0.5053. Farhan is in fourth place with a score of 0.5. Furthermore, Siti took fifth place with a score of 0.4448, followed by Laila in sixth place with a score of 0.4172. Dewi is in seventh position with a score of 0.352, while Ahmad is in last position with the lowest score, which is 0.0928.